Penerapan Program Weekly Rate Sebagai Bentuk Intervensi Mikro pada Anak di UPT SD Negeri 067099 Medan - Juwita Enjelina Panjaitan; Gusti Pirandy (Yayasan Literasi Sains Indonesia, 2023)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students can actively develop their potential to have religious spiritual strength, personality, self-control, and skills. Primary school education is the education of children aged 7 to 13 years as education at the basic level developed in accordance with the education unit, regional potential, and socio-culture. The family is the first and main education base for children. It is important for a child to gain basic knowledge, psychological development and physical growth. Most of a child's life is spent in the family so that the educational experience gained from the family will affect the next educational process. Therefore, parents must be able to instill good and correct education, and be responsible for their children. Weekly rate is an activity to record things experienced by grade 4 students every week. The note must be filled in by students before school dismissal time. Where the output of this program is to be able to carry out a micro-level-based intervention process for students in need in the field of education.